Evaluasi Program Pembinaan Olahraga Tenis Lapangan di Kabupaten Sekadau - Perani, Ilham; Maksum, Henry; Daryanto, Zusyah Porja (Journal Sport Academy, 2022)
Abstract This study aims to evaluate (1) context which includes the dissemination of information, government and community support, availability of human resources (2) Input includes the selection of athletes, coaches and assistant coaches, feasibility of facilities and infrastructure, financing the implementation of coaching programs (3) Process includes the implementation of training programs, promotion and degradation systems, coordination, welfare, and transportation, (4) Product includes the success of coaching programs, regional achievements, and regional achievements, national and international achievements. The approach used in this program evaluation research is the CIPP Model (Stufebeam's) in terms of the Context, Input, Process and Product stages. The evaluation research method uses a mixed or elective design. This research resulted in the findings (1) The context of the tennis field coaching program in Sekadau Regency is already in good condition (43%), (2) The input of the tennis field coaching program in Sekadau Regency is already good (58%). (3) The process of the tennis sport coaching program which was implemented in general has been going well (42.8%). (4) The product of the tennis sports coaching program is good (45%). It can be concluded that overall the coaching program is not good (52.8%). The conclusions from the results of the study are that the context, the quality of the inputs, processes and products of tennis sports coaching in Sekadau Regency are already in good condition.